Subacute Sclerosing Panencephalitis - Banik, Gobinda Chandra; Aman, Sakib; Sultana, Farhana; Mohammad Arif, Syed (Journal of Bangladesh College of Physicians and Surgeons, 2019)
Subacute sclerosing panencephalitis (SSPE) is chronic progressive encephalitis of childhood and young adoloscent due to persistent measles virus infection. This case illustrates a 14 year old girl presented with short history of intellectual decline, abnormal behavior, myoclonus and altered consciousness with suggestive neuroimaging mimicking metachromatic leucodystrophy. Subsequently she was diagnosed to be a case of Subacute sclerosing panencephalitis (SSPE) on the basis of Electroencephalography (EEG) and Cerebrospinal fluid(CSF) measles antibody titer. J Bangladesh Coll Phys Surg 2019; 37(4): 205-208